Metastasis Kanker Paru: [Lung Cancer Metastatic] - Anna Febriani; Achmad Furqon (Jurnal Respirasi, 2018)
Metastasis is the ability of cells to escape from the primary tumor, then enter the circulation to the distant tissue and form a secondary tumor. There are hemodynamic hypothesis (anatomical) and seed and soil hypothesis (molecular recognition). Tumor cells spread through several ways: percontinuitatum, lymphogen, hematogenous, transluminal, transcelomic, and iatrogenic. The stages of the metastasis process include: detachement, invasion, intravasation, circulation, extravasation, and angiogenesis. Predilection of lung cancer metastasis often happens in the brain, bones, liver, and adrenal glands. The spread of lung cancer metastasis to the brain, bone, and liver occurs hematogenously. Adrenal glands metastasis ipsilateral occurs lymphatically, while contralateral occurs hematogenously. Lung cancer is often diagnosed at an advanced stage, because in the early stage it is often asymptomatic. Metastasis of lung cancer to distant organs is the most cause of lung cancer deaths.